Studi Tingkat Kehilangan Air Minum Perumda Air Minum Tirta Moedal Kota Semarang Dengan Neraca Air Wb-Easycalc dan Infrastructure Leakage Indeks (ILI) - Muhammad Sidiq Nur Harenda; Ervin Nurhayati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Perumda Air Minum Tirta Moedal, the manager of the drinking water supply system in the city of Semarang, is facing the challenge of controlling high water losses. In 2022, the company reported a water loss value or NRW of 48.41%. This NRW is much higher than the national NRW reduction target of 20%, so it is necessary to take measures to reduce NRW. This research aims to conduct a water balance analysis and Infrastructure Leakage Index (ILI) assessment to provide recommendations and evaluation of the water loss control programme implemented by Perumda Air Minum Tirta Moedal. The research method used is data analysis using the WB-EasyCalc application to obtain NRW and ILI values. In 2023, the amount of water distributed will be 103,830,494 m3. The collected water amounts to 54,384,744 m3. According to calculations based on the water balance, the water loss in 2023 will be 49,445,750 m3/year (47.62%). Based on the ILI assessment, Perumda Air Minum Tirta Moedal received a score of 44.7 with an average daily pressure of 11.2 metres. The ILI score indicates that Perumda Air Minum Tirta Moedal is in Category D, which means that there is an extraordinary waste of resources and that water loss must be controlled immediately. Recommendations for controlling water loss through evaluation and improvement of existing programmes. Programme improvements include DMA evaluation, customer meter survey and calibration, and pressure management improvements.